Details our eyes cannot see: Challenges for the analysis of body position during bicycle fitting - Bini, R. R.; Encarnación-Martínez, A.; Priego-Quesada, J. I.; Carpes, F. P. (Sports Biomechanics, 2023)
Bicycle fitting is popular and largely beneficial to a range of cyclists, but consistency in methods to assess posture of cyclists on their bicycles is lacking. This is critical because decisions on if and how to change bicycle fitting are largely dependent on the validity and reliability of assessment outcomes. Therefore, we propose that